Platelet Activating Factor Enhances Synaptic Vesicle Exocytosis Via PKC, Elevated Intracellular Calcium, and Modulation of Synapsin 1 Dynamics and Phosphorylation - Hammond, Jennetta W.; Lu, Shao-Ming; Gelbard, Harris A. (Frontiers in Cellular Neuroscience, 2016)
Platelet activating factor (PAF) is an inflammatory phospholipid signaling molecule implicated in synaptic plasticity, learning and memory and neurotoxicity during neuroinflammation. However, little is known about the intracellular mechanisms mediating PAF’s physiological or pathological effects on synaptic facilitation. We show here that PAF receptors are localized at the synapse. Using fluorescent reporters of presynaptic activity we show that a non-hydrolysable analogue of PAF (cPAF) enhances synaptic vesicle release from individual presynaptic boutons by increasing the size or release of the readily releasable pool and the exocytosis rate of the total recycling pool. cPAF also activates previously silent boutons resulting in vesicle release from a larger number of terminals. The underlying mechanism involves elevated calcium within presynaptic boutons and protein kinase C (PKC) activation. Furthermore, cPAF increases synapsin I phosphorylation at sites 1 and 3, and increases dispersion of synapsin I from the presynaptic compartment during stimulation, freeing synaptic vesicles for subsequent release. These findings provide a conceptual framework for how PAF, regardless of its cellular origin, can modulate synapses during normal and pathologic synaptic activity.